"We're going to show up:" examining the work of a white antiracist organization. Issue 1 (2nd January 2021) - Diebold, Josal
ABSTRACT: In responding to the calls of generations of leaders of color, white antiracists have committed to accountably organizing their own communities to dismantle white supremacy. Yet, there has been a dearth of research on white antiracist community organizing, specifically. Thus, this study, based on principles of community-based participatory research, sought to investigate the work of a white antiracist organization over the course of a year, using focus groups, open-ended surveys, and meeting notes. The data were qualitatively analyzed, resulting in 4 categories that describe the organization's efforts, accomplishments, and growing edges. Limitations and implications are discussed.